2022
DOI: 10.3390/jcdd9080275
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Isolation in Obese Compared to Non-Obese Patients: Real-Life Experience from a Large Tertiary Center

Abstract: 1. Introduction: Pulmonary vein isolation (PVI) is an established procedure used to achieve rhythm control in atrial fibrillation (AF). In obese patients (pts), in whom AF occurs more frequently, a reduced effectiveness of PVI has been observed. Therefore, this study’s aim was to compare the long-term efficacy of PVI between obese and non-obese patients. 2. Methods: We enrolled 111 consecutive pts with a body mass index (BMI) of >30 kg/m2 undergoing PVI from our large registry. Procedural data and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
(23 reference statements)
3
6
0
Order By: Relevance
“…The current study finding is consistent with the study of Wolfes et al (2022), who reported that respect interventions are important human resource management practices for preventing mistreatment. However, little is known about what influences the effectiveness of respect training.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study finding is consistent with the study of Wolfes et al (2022), who reported that respect interventions are important human resource management practices for preventing mistreatment. However, little is known about what influences the effectiveness of respect training.…”
Section: Discussionsupporting
confidence: 93%
“…Avoid moral and ethical problems by raising awareness of respect as an essential characteristic of the workplace key areas in need of attention are nurses' compliance with professional values through following of code of ethics and ethical principles. Wolfes et al (2022). reported that the majority of nurses score high on the professional values scale in nursing subscales and reported that all items on the professional values scale in nursing nurses are essential concluding that education in nursing plays a vital role in acquiring and maintaining values The current study found a positive correlation between staff nurses' professional values, awareness of moral and moral issues, and respect (knowledge, self-assessment) among all head nurses at different testing times.…”
Section: Discussionmentioning
confidence: 49%
“…A limited number of previous studies aimed at investigating the influence of obesity on atrial fibrillation ablation have been published so far [6] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] and data focusing on PVI efficacy in CMD patients are limited [18] , [19] , [20] , [21] , [40] .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of AF, on one hand side increasing body mass index (BMI) increases the risk of AF occurrence [5] and on the other hand possibly diminishes efficacy and safety of pulmonary vein isolation (PVI) for AF management. [6] , [7] , [8] , [9] , [10] , [11] , [12] Nevertheless, data are equivocal as some authors have recently reported equivalent efficacy and safety of CBA for PVI in obese patients [13] , [14] , [15] , and there is evidence suggesting adequate rates of sinus rhythm maintenance after PVI in obese patients only with effective weight reduction. [16] , [17] Moreover, patients with diabetes as main CMD have an approximately 35% increased risk of developing AF (particularly with poor glycemic control) [18] and a higher recurrence rate correlating with elevated glycosylated hemoglobin after AF ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the procedural success and complication rates were similar in patients with normal, mildly reduced, or mild to moderate reduction in glomerular filtration rate [ 60 ]. A case-control study showed that obese patients did not have higher AF recurrence rates after CA compared to patients with normal body weight, suggesting that body mass index alone may not be a criterion for refusing catheter ablation [ 61 ]. Beyond catheter ablation’s efficacy in arrhythmia recurrences, some recent studies have explored the interesting association between AF and dementia and the possible role of rhythm control strategies in preventing cognitive decline [ 62 , 63 ].…”
mentioning
confidence: 99%